IMPLEMENTASI AKAD MURABAHAH PADAPEMBIAYAAN KREDIT USAHA RAKYAT /KUR (BANK SYARIAH INDONESIA DI KCP TRUNOJOYO 2 KABUPATEN SUMENEP) - Sudianto Sudianto; Astri Ningsih; Helya Aufin Mizatina (Al-Amien Prenduan for Islamic Institute, 2022)
This research aims for know implementation contract murabahah on financing credit business people (KUR) at Bank Syariah Indonesia at KCP Trunojoyo 2 district sumenep . KUR is financing provided _ to MSMEs for working capital and investment to individual or productive group . _ Study this use method qualitative descriptive with technique data collection through interviews , observations , and documentation . Results from research that has been carried out to prove that application contract murabahah on KUR financing at BSI KCP Trunojoyo 2 is carried out by two contract that is contract wakalah first then To do second contract _ that is murabahah . Socialization _ implementation KUR financing is always carried out, stages application customer by agreement financing , BI checking , surveys, analyzing , disbursing , monitoring , early warning before maturity is the right way to minimize financing contract constraints on KUR.